Mindfulness: Unpacking its three shades and illuminating integrative ways to understand the construct. (22nd April 2022) - Daniel, Carole; Walsh, Isabelle; Mesmer‐Magnus, Jessica
Abstract: Over time mindfulness research and practice has taken on diverse basic assumptions and theoretical traditions, and the pseudo‐scientific use of the term has become more prevalent. Given the ubiquitousness of both personal and professional applications of mindfulness, the need for a thorough understanding of its theoretical cornerstones is necessary. In this review, we use bibliometric techniques to uncover the field's intellectual roots (Study 1), and document bibliographic coupling analysis to illuminate current research avenues across management disciplines (Study 2). Our bibliometric process covers 48 references for co‐citation and 238 articles for bibliographic coupling analyses, respectively, published between 2012 and 2020. Co‐citation analysis reveals a shift of focus from the past two historical mindfulness schools of thought (Eastern and Western) to a novel intellectual structure of the mindfulness field articulated around three distinct yet overlapping research streams. We propose integrative ways to advance mindfulness research by unpacking mindfulness processes, dimensions and development, arguing that the integration of these three main foci is necessary to advance understanding of mindfulness. Bibliometric coupling analysis identifies eight management‐related mindfulness research themes. We discuss the extent to which these eight themes have comparably explored the three foci (mindfulness processes, dimensions and development) highlighted in our model. Lastly, we use our theory‐driven review to draw on under‐developed areas of research, identifying profitable directions for future research on mindfulness in the workplace and beyond.